Nanosecond diagnostics of proton beam current impulse with wall current monitor on MMF LINAC - Men’shov, A.A.; Novikov-Borodin, A.V.; Yin, Y. (Вопросы атомной науки и техники, 1999)
The described device now operates at the MMF H+ beam transport line. A number of physics experiments with pulse neutron sources have been done successfully. The design of such a device for the MMF H- beam transport line is needed.